German labor market reform and the rise of Eastern Europe: dissecting their effects on employment - Timo Walter (Empirica, 2023)
From the early 1990s until 2005 the unemployment rate rose in Germany from 7.3 to 11.7%. While the unemployment rate reached its peak in 2005, it decreased steadily in the following years. The fourth stage of the German labor market reform (Hartz IV) was implemented in 2005 with the intent to cut the unemployment rate. This paper investigates the employment and welfare effects of the Hartz IV reform. Moreover, I am interested in the employment impact of German labor market reform due the rise of the East, which is the productivity increase in Germany and Eastern Europe that has fostered joint fast-growing trade. The focus lies on the national and county level (including 402 counties). As the effects on regional labor markets differ and take time, the paper builds on the dynamic and spatial trade model of Caliendo et~al. ( 9 ). I find that the Hartz IV reform is responsible for a 25% drop in unemployment, with a particular impact on eastern German counties. The rise of the East leads to an additional positive contribution to the labor market.
Keywords: F14; F16:F17; 330; Dynamic trade model; Labor market reform; Productivity shocks; Welfare implications; Germany; Eastern Europe